Impementing Self-Study Review Feedback - Margaret A Thomas-Evans; Denise Bullock (Academic Chairpersons Conference Proceedings, 2019)
Department Chairs who are writing a self-study or program review will benefit from this session on implementing self-study review feedback and learn how to leverage feedback to argue for new hires, additional resources for projects, and support for worthwhile initiatives.
Keywords: Self-Study; Program Review; Accreditation; Feedback